Excess Ub-K48 Induces Neuronal Apoptosis in Alzheimer’s Disease - Qiang Li; Yiyuan Yuan; Shi Huang; Guangfu Di; Haoyuan Chen; Yani Zhuang; Wanzhen Fang; Yanjiao Huang; Yinan Tao; Jing Jiang; Zhiliang Xu (Journal of Integrative Neuroscience)
Background: K48-linked ubiquitin chain (Ub-K48) is a crucial ubiquitin chain implicated in protein degradation within the ubiquitin-proteasome system. However, the precise function and molecular mechanism underlying the role of Ub-K48 in the pathogenesis of Alzheimer’s disease (AD) and neuronal cell abnormalities remain unclear. The objective of this study was to examine the function of K48 ubiquitination in the etiology of AD, and its associated mechanism of neuronal apoptosis. Methods: A mouse model of AD was constructed, and behavioral phenotypic changes were detected using an open field test (OFT). The expression of glial fibrillary acidic protein (GFAP), an early marker of AD, was detected by western blotting (WB). Neuronal apoptosis in the hippocampal region was assessed by hematoxylin and eosin (HE) and Nissl staining. Immunohistochemistry and immunofluorescence were performed to observe the changes in Phosphorylated tubulin associated unit (p-Tau) and Ub-K48 colocalization in neurons of the hippocampal region of AD mice. WB was further applied to detect the degree of ubiquitylation of K48 and the expression of Tau, p-Tau, B-cell lymphoma-2 (Bcl-2) and Bcl-2-associated X (Bax) proteins in neuronal cells of the hippocampus and cortical regions of mice. Results: Mice with AD exhibited significantly longer resting times (p < 0.05) and shorter average speeds (p < 0.01), total distances travelled (p < 0.01), and distances travelled (p < 0.01) in the central region than those in the control group. This indicated cognitive impairment, which occurred concurrent with an increased expression of the AD marker GFAP protein (p < 0.001). The hippocampal region of AD mice showed abnormalities with sparsely and irregularly arranged cells, large gaps between cells, lighter staining, unclear boundaries of the cell membranes and nuclei, and agglutinated and condensed nuclei (p < 0.01). The neuronal cells of AD mice exhibited significantly elevated levels of p-Tau (p < 0.01) and Ub-K48 (p < 0.01), as well as a notable degree of co-localization within the cells. The intracellular pro-inflammatory protein Bax was significantly upregulated (p < 0.05), while the Bcl-2/Bax ratio was significantly lower than that in the control group (p < 0.05), thus inducing apoptosis in AD neuronal cells. Conclusion: Ub-K48 is strongly linked to the development of AD. p-Tau aggregate in neuronal cells in the hippocampal region of the AD brain and colocalize with Ub-K48, which in turn leads to cellular inflammation and the induction of apoptosis in neuronal cells.